THE LEARNING OF TAKING CARE OF THE CHILD'S FAMILY HOSPITALIZED BY GROUP ACTIVITIES - Carla Natalina da Silva Fernandes; Lourdes Maria da Silva Andraus; Denize Bouttelet Munari (Universidade Federal de Goias, 2006)
SUMMARY: This study aims to know the student's learning in the process of taking care of the relative companion of hospitalized child/adolescent. This is a qualitative design of descriptive and exploratory research. The investigation was accomplished with 12 academic of the 5th of the nursing graduation class at the Federal University of Goiás. The data collection was made by a semi-structured interview applied to the students from December 2004 to January 2005. The analysis was based on thematic analysis which allowed the identification of two categories: 1) Understanding nurses academic formation to care families, that it explores the way as students notices them formation to take care of the child and of her family and 2) The meaning of caring by group strategies, that detaches aspects of the learning of the use of activities in group with relatives. In the students' perspective, that was an important experience for providing moments to stay together and facilitating the care offered to the child and family, as well as it made possible the reflection about the necessary abilities to think and to do the humanized care in the context of the established relationships among family-patient-nurses. The students still detach some aspects that feel need of improvements from teachers and of the health institution, showing the relevance to consider the student's evaluation as an instrument for constant renewal of the pedagogic practices, as well as for the improvement of the quality of the attendance in health. KEY WORDS: Pediatric Nursing; Higher Education; Group Processes